2022
DOI: 10.3390/jcm12010027
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of the Commercial Probiotic Blend Synbio® for the Management of Vaginal Dysbiosis

Abstract: A healthy vaginal microbiota is Lactobacillus-dominated. Several factors can interfere with the state of balance leading to dysbiosis, such as vaginal infections caused by bacteria and Candida species. The present single-arm, uncontrolled open-label study aimed to evaluate the ability of the SYNBIO® probiotic combination, taken as an oral formulation, to contribute to vaginal health. Thirty pre-menopausal participants were included in the study. Participants were instructed for daily oral intake of SYNBIO® pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…L. acidophilus, L. rhamnosus, and L. reuteri are used as raw materials in healthy functional foods (daily intake of 10 8 -10 10 CFU) according to Health Functional Food Standards, Ministry of Food and Drug Safety. In another study, administering a 1:1 combination of L. rhamnosus IMC 501 ® and Lactobacillus paracasei IMC 502 ® (5 × 10 9 CFU/capsule/day for 15 consecutive days) improved leucorrhea, itching, and vulvo-vaginal erythema/edema [29]. In the present study, L. acidophilus, L. rhamnosus and L. reuteri abundance showed a decrease at visit 2 (Figure 6).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…L. acidophilus, L. rhamnosus, and L. reuteri are used as raw materials in healthy functional foods (daily intake of 10 8 -10 10 CFU) according to Health Functional Food Standards, Ministry of Food and Drug Safety. In another study, administering a 1:1 combination of L. rhamnosus IMC 501 ® and Lactobacillus paracasei IMC 502 ® (5 × 10 9 CFU/capsule/day for 15 consecutive days) improved leucorrhea, itching, and vulvo-vaginal erythema/edema [29]. In the present study, L. acidophilus, L. rhamnosus and L. reuteri abundance showed a decrease at visit 2 (Figure 6).…”
Section: Discussionsupporting
confidence: 63%
“…Specific probiotics, such as Lactobacillus probiotics (LBPs), are suggested to have safe and promising therapeutic effects to modulate microbiota homeostasis in the general population [27]. Studies have shown that oral LBP intake not only improves vaginal microbiota dysbiosis significantly, but also improves leucorrhea, itching, and vulvo-vaginal erythema/edema [28,29]. In addition, Lactobacillus surface active molecules (peptidoglycan, lipoteichoic acid, exopolysaccharides, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Participants taking daily oral probiotic lactobacilli capsules can lead to a substantial improvement in the vaginal flora in terms of an increase in lactobacilli and a decrease in enterococci, staphylococci, Gardnerella spp., and Candida spp. in mixed vaginal infected patients ( Pino et al., 2022b ; Rapisarda et al., 2023 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%